Optimization of blood pressure measurement practices for pharmacodynamic analyses of tyrosine‐kinase inhibitors - Maddalena Centanni; Abel Thijs; Ingrid Desar; Mats O. Karlsson; Lena E. Friberg (Wiley, 2023)
Abstract Blood pressure measurements form a critical component of adverse event monitoring for tyrosine kinase inhibitors, but might also serve as a biomarker for dose titrations. This study explored the impact of various sources of within‐individual variation on blood pressure readings to improve measurement practices and evaluated the utility for individual‐ and population‐level dose selection. A pharmacokinetic-pharmacodynamic modeling framework was created to describe circadian blood pressure changes, inter‐ and intra‐day variability, changes from dipper to non‐dipper profiles, and the relationship between drug exposure and blood pressure changes over time. The framework was used to quantitatively evaluate the influence of physiological and pharmacological aspects on blood pressure measurements, as well as to compare measurement techniques, including office‐based, home‐based, and ambulatory 24‐h blood pressure readings. Circadian changes, as well as random intra‐day and inter‐day variability, were found to be the largest sources of within‐individual variation in blood pressure. Office‐based and ambulatory 24‐h measurements gave rise to potential bias (>5 mmHg), which was mitigated by model‐based estimations. Our findings suggest that 5-8 consecutive, home‐based, measurements taken at a consistent time around noon, or alternatively within a limited time frame (e.g., 8.00 a.m. to 12.00 p.m. or 12.00 p.m. to 5.00 p.m.), will give rise to the most consistent blood pressure estimates. Blood pressure measurements likely do not represent a sufficiently accurate method for individual‐level dose selection, but may be valuable for population‐level dose identification. A user‐friendly tool has been made available to allow for interactive blood pressure simulations and estimations for the investigated scenarios.